2009
DOI: 10.1183/09031936.00065009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabis on lung function: a population-based cohort study

Abstract: The effects of cannabis on lung function remain unclear and may be different from those of tobacco. We compared the associations between use of these substances and lung function in a population-based cohort (n=1,037). Cannabis and tobacco use were reported at ages 18, 21, 26 and 32 yrs. Spirometry, plethysmography and carbon monoxide transfer factor were measured at 32 yrs. Associations between lung function and exposure to each substance were adjusted for exposure to the other substance. Cumulative cannabis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

19
164
1
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(193 citation statements)
references
References 27 publications
19
164
1
9
Order By: Relevance
“…These findings are consistent with those of a few previous investigators who have shown a significant relationship between marijuana use and an increase in FVC (8,9), as well as increases in FRC, TLC, and residual volume (8). The mechanism for the increased lung volumes associated with marijuana smoking is speculative but may be a result of stretching the lung from the repeated deep inhalations associated with the usual technique of smoking marijuana, in which inhaled volumes are significantly larger and breathholding times after deep inhalations are much longer compared with the usual topography for smoking tobacco cigarettes (15).…”
supporting
confidence: 82%
See 4 more Smart Citations
“…These findings are consistent with those of a few previous investigators who have shown a significant relationship between marijuana use and an increase in FVC (8,9), as well as increases in FRC, TLC, and residual volume (8). The mechanism for the increased lung volumes associated with marijuana smoking is speculative but may be a result of stretching the lung from the repeated deep inhalations associated with the usual technique of smoking marijuana, in which inhaled volumes are significantly larger and breathholding times after deep inhalations are much longer compared with the usual topography for smoking tobacco cigarettes (15).…”
supporting
confidence: 82%
“…This conclusion is generally supported by the results of longitudinal studies, although the latter are few in number (8,16).…”
supporting
confidence: 76%
See 3 more Smart Citations